Kidnap for ransom : resolving the unthinkable - Wright, Richard P. (CRC Press, 2009)
"Kidnap for Ransom: Resolving the Unthinkable removes the veil of mystery and dispels some of the myths surrounding kidnapping. The book provides security professionals and law enforcement personnel with the modern tools needed to understand and effectively respond to the crime of kidnapping." "Offering extensive use of actual case histories, this is the first book to examine the kidnap for ransom phenomenon and to reveal the process from the moment of the kidnapping until the victim's safe return. The author's experience as the principal consultant and manager in the successful resolution of numerous kidnapping and extortion incidents makes this book an invaluable tool for those charged with the responsibility of kidnap prevention, as well as for those law enforcement agents called on to mitigate the potential consequences of an abduction in progress."--BOOK JACKET.